Konstelasi Politik Pasca Perang Ngali di Bima - Sukarddin Sukarddin; Mulyati Mulyati; Faujiah Faujiah (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2020)
Sultanate of Bima faces various challenges, especially in the economic and political fields of government. Trade freedom had been the main pillar of the economy, threatened by the Dutch trade monopoly. Sovereignty and territorial integrity are threatened by the